ANALYSIS OF FINANCIAL ACCOUNTING STANDARDS FOR SMALL AND MEDIUM MICRO ENTITIES (MSMEs) IN THE IMPLEMENTATION OF SENDYCA KONVEKSI MSME FINANCIAL REPORTING - Casella, Senna Indri; Marini, Yushita (Accounting and Business Journal; Vol 5 No 2 (2023): ACCOUNTING AND BUSINESS JOURNALDO - 10.54248/abj.v5i2.4719, 2024)
A financial accounting standard called SAK EMKM is available to Assist Micro, Small and Medium Enterprises (MSMEs) in preparing financial reports. Four stages of data collection were used: observation, data reduction, data presentation, interviews, and drawing conclusions. The aim of this research is to find out how the financial reports of Sendyca Konveksi Assist Micro, Small and Medium Enterprises (MSMEs) can benefit from implementing SAK EMKM. Three financial report components are included in the SAK EMKM application when presenting financial reports: Financial Report Notes, Financial Position Report, and Profit and Loss Report.